Analysis of Potential Alternative Energy Sources for Electricity Conservation in Yogyakarta State Finance Building - Anna Nur Nazilah Chamim; Rahmat Adiprasetya Al Hasibi; Agus Jamal; Siva Aprilia; Yessi Jusman; Jeckson Jeckson (Universitas Muhammadiyah Yogyakarta, 2019)
State Finance Building of Yogyakarta is a community service that is included in the types of buildings that consume electric energy that is large, so that often led to the power outage unexpectedly due to excessive use of electricity. This excessive use of electricity has also contributed to bill accounts for electricity from PLN which each month up to hundreds of millions of dollars. To that end, this research was undertaken that aim to be able to device that most optimal configuration in the use of solar panels and could compare the PLTS system between On-Grid and PLN in the aspect of cost and CO2 emissions.In knowing the potential of alternative energy sources, namely solar power connected to the PLN as the optimal power plant is carried out by means of conducting research in the form of knowing the intensity of the solar radiation data, data in the form of electric power load is active for 24 hours, and data rates time of outside peak load and time of peak load from PLN for State Finance Building Of Yogyakarta. Later, she did the simulation using software to help homer modeling from use of the most optimal solar panel. In the research results obtained that the potential PLTS system that are connected with the grid PLN unfit to be carried out because the cost of the initial investment to expenses during the period of operation of the system including the high value of the NPC of 970,742. However, the potential of the power plant that are appropriate for the conditions on site research solar power plant was connected to the grid PLN power plant configuration that is optimized for without using batteries, use only PV with a capacity of 91,35 kW, the converter with a capacity of 400 kW, and power grid network of PLN the system transmitted to PLTS On-Grid of 552 kW.